Amygdaloid theta-band power increases during conflict processing in humans. (September 2021) - Tang, Austin M.; Chen, Kuang-Hsuan; Gogia, Angad S.; Del Campo-Vera, Roberto Martin; Sebastian, Rinu; Gilbert, Zachary D.; Lee, Yelim; Nune, George; Liu, Charles Y.; Kellis, Spencer; Lee, Brian
Highlights: Amygdaloid theta band power increases in situations requiring non-emotional conflict resolution. Stereo electroencephalography offers high resolution access to recording neural signals in the human amygdala. Abstract: The amygdala is a medial temporal lobe structure known to be involved in processing emotional conflict. However, its role in processing non-emotional conflict is not well understood. Previous studies have utilized the Stroop Task to examine brain modulation of humans under the color-word conflict scenario, which is non-emotional conflict processing, and found hippocampal theta-band (4–7 Hz) modulation. This study aims to survey amygdaloid theta power changes during non-emotional conflict processing using intracranial depth electrodes in nine epileptic patients (3 female; age 20–62). All patients were asked to perform a modified Stroop task. During task performance, local field potential (LFP) data was recorded from macro contacts sampled at 2 K Hz and used for analysis. Mean theta power change from baseline was compared between the incongruent and congruent task condition groups using a paired sample t -test. Seven patients were available for analysis after artifact exclusion. In five out of seven patients, statistically significant increases in theta-band power from baseline were noted during the incongruent task condition (paired sample t -test p < 0.001), including one patient exhibiting theta power increases in both task conditions. Average response time was 1.07 s (failure trials) and 1.04 s (success trials). No speed-accuracy tradeoff was noted in this analysis. These findings indicate that human amygdaloid theta-band modulation may play a role in processing non-emotional conflict. It builds directly upon work suggesting that the amygdala processes emotional conflict and provides a neurophysiological mechanism for non-emotional conflict processing as well.